Community education on Diabetes Mellitus in Taratara Satu Village, Tomohon Barat District, Indonesia - Maddusa, Sri Seprianto; Rumengan, Adeleide; Sabandar, Fridela; Lantho, Graselin; Sinaga, Patricia; Lintong, Kheren; Polii, Okan (Sociality: Journal of Public Health Service, 2025)
Diabetes Mellitus (DM) is a major global health issue, with rising prevalence linked to lifestyle factors. In Indonesia, DM was the third leading cause of mortality in 2019, and cases are projected to increase by 47% by 2045. Given these concerns, community education plays a crucial role in enhancing public awareness regarding DM prevention and management. This program aimed to enhance community knowledge about DM risks in Taratara Satu Village, Tomohon Barat District. A pre-experimental one-group pretest-posttest design was used, involving 12 DM-diagnosed respondents. The intervention included a pre-test, door-to-door education using lectures and visual media, and a post-test. Data were analyzed descriptively to assess knowledge improvement. Before the intervention, 58.33% of participants had good knowledge, while 41.67% had moderate knowledge. After the program, 91.67% demonstrated good knowledge, showing a significant improvement. The educational program successfully enhanced public knowledge about Diabetes Mellitus in Taratara Satu Village. The intervention proved effective in increasing awareness of DM risk factors, symptoms, and prevention strategies. This study underscores the importance of continuous community education to promote healthier lifestyles and reduce DM prevalence.